The geothermal occurrence of Kapistri, Ierapetra area, Crete - Chatzigiannis, G.; Kavouridis, Th. (Bulletin of the Geological Society of Greece, 2013)
The geothermal occurence is located close to the Kapistri village, Ierapetra town, prefecture of Lassithi. In some water wells temperature of about 25oC in a depth of 100 - 150 m below surface, were measured. The calculated geothermal gradient is thus double in size compared to normal gradient. The geological environment is composed of platy limestones of the autochthonous series of Crete on which units of phyllite – quartzite series as well as Pindos and Tripoli zones are overthrusted. Granite intrusion occurs in the carbonates with distinct contact metamorphism, in the Kapistri area. Intense tectonic activity is observed in the wider area of the Ierapetra graben with main fault direction N – S, E –W, NW – SE, and NE – SW. The elevated geothermal gradient, the intense faulting of the area and the existence of deep circulated water indicates the development of a deeper geothermal field.